2015
DOI: 10.15537/smj.2015.10.12403
|View full text |Cite
|
Sign up to set email alerts
|

Sedation in hypoalbuminemic geriatric patients under spinal anesthesia in hip surgery

Abstract: Objectives:To compare midazolam and propofol sedation in hypoalbuminemic geriatric patients under spinal anesthesia in hip surgery with bispectral index monitoring.Methods:This prospective and randomized study was completed in the Department of Anesthesiology, Okmeydani Training and Research Hospital, Istanbul, Turkey between February 2013 and December 2014. Sixty patients undergoing elective hip surgery under spinal anesthesia in the geriatric age group with albumin levels below 3 g/dl were randomly divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…This undesired outcome is eliminated by sedating the patients during the operation. Sedation is possible through inhalation or bolus or continuous infusion of pharmacological agents injected intravenously [10]. …”
Section: Discussionmentioning
confidence: 99%
“…This undesired outcome is eliminated by sedating the patients during the operation. Sedation is possible through inhalation or bolus or continuous infusion of pharmacological agents injected intravenously [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Fewer hemodynamic changes in PCSNB cases when compared with CSA cases were also noted [91]. A 2015 prospective randomized study comparing midazolam with propofol sedation in hypoalbuminemia (albumin level below 3 g/dl) geriatric patients under SA found that when compared with midazolam, propofol is associated with greater hemodynamic stability, lesser respiratory depression, and faster recovery [92].…”
Section: Mode Of Anesthesiamentioning
confidence: 93%